Spheromaks : a practical application of magnetohydrodynamic dynamos and plasma self-organization - Bellan, Paul Murray, 1948- (Imperial College Press, 2000)
"Spheromaks are easily formed, self-organized magnetized plasma configurations that have intrigued plasma physicists for over two decades." "This book begins with a review of the basic concepts of magnetohydrodynamics and toroidal magnetic configurations, then provides a detailed exposition of the 3D topological concepts underlying spheromak physics, namely magnetic helicity, Taylor relaxation, force-free equilibria, and tilt stability. It then examines spheromak formation techniques, driven and isolated configurations, dynamo concepts, practical experimental issues, diagnostics, and a number of applications. The book concludes by showing how spheromak ideas are closely related to the physics of solar prominences and interplanetary magnetic clouds."--Jacket